1997
DOI: 10.1128/jcm.35.12.3166-3170.1997
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical and epidemiological significance of enterococci intrinsically resistant to vancomycin (possessing the vanC genotype)

Abstract: Constitutive low-level vancomycin resistance is found intrinsically in certain enterococcal species and is encoded by vanC ligase genes. These intrinsically vancomycin-resistant enterococci (VRE) will be referred to as VANC VRE. A prospective study to determine the clinical and epidemiologic significance of VANC VRE was conducted. VANC VRE were recovered from the stools of 34 of 601 (5.7%) patients, a rate similar to that obtained for the stools of 100 outpatients in the community (5%). VANC VRE were also isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
35
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(36 citation statements)
references
References 30 publications
(36 reference statements)
1
35
0
Order By: Relevance
“…This finding has im- portant implications for the clinical microbiology laboratory. E. gallinarum is pathogenic for humans (21,22); in a recent study, enterococci with vanC-associated vancomycin resistance were isolated from nonstool specimens of 9 of 538 patients (1.7%), including two patients with bacteremia who subsequently died (27). Furthermore, vancomycin treatment failure has been associated with intrinsic low-level vancomycin resistance both in humans and in animal models of experimental endocarditis (8,12,15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This finding has im- portant implications for the clinical microbiology laboratory. E. gallinarum is pathogenic for humans (21,22); in a recent study, enterococci with vanC-associated vancomycin resistance were isolated from nonstool specimens of 9 of 538 patients (1.7%), including two patients with bacteremia who subsequently died (27). Furthermore, vancomycin treatment failure has been associated with intrinsic low-level vancomycin resistance both in humans and in animal models of experimental endocarditis (8,12,15).…”
mentioning
confidence: 99%
“…There therefore exists a need to accurately and quickly differentiate enterococci with vanCassociated vancomycin resistance from vancomycin-susceptible enterococci. On the other hand, it has been suggested that vanC-associated vancomycin resistance is not a concern for infection control, because no nosocomial transmission of the involved organisms has been reported (27)(28)(29). Costly and cumbersome infection control precautions, such as those recommended for enterococci with vanA-and vanB-associated vancomycin resistance, may therefore not be necessary in the management of patients with vanC enterococci (9,11,13,16).…”
mentioning
confidence: 99%
“…Recent reports have demonstrated the inability of many clinical laboratories (2,23,34) and commercial susceptibility testing systems (12,23,34) to detect glycopeptide resistance, especially patterns of low-or moderate-level resistance to vancomycin in enterococci (strains with a vanC genotype and certain strains of the vanB type). Enterococci with the vanC genotype, i.e., E. gallinarum and E. casseliflavus, which possess an intrinsic property of constitutive low-level VR (13,19), are infrequently recovered from clinical specimens (11,32). The clinical significance of resistance expressed by these organisms, as opposed to the significance of that expressed by vanA or vanB, or HLAR enterococci, remains unclear (32), and the implications of susceptible or intermediate vancomycin results for isolates of these species are also uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Enterococci with the vanC genotype, i.e., E. gallinarum and E. casseliflavus, which possess an intrinsic property of constitutive low-level VR (13,19), are infrequently recovered from clinical specimens (11,32). The clinical significance of resistance expressed by these organisms, as opposed to the significance of that expressed by vanA or vanB, or HLAR enterococci, remains unclear (32), and the implications of susceptible or intermediate vancomycin results for isolates of these species are also uncertain. A laboratory report of a VR isolate will initiate a cascade of infection control events that are both time-consuming and costly (5) and that should be focused on organisms of the vanA or vanB pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation